Properties of DLC coatings deposited by DC and DC with superimposed pulsed vacuum arc - Zavaleyev, V.; Walkowicz, J.; Aksyonov, D.S.; Luchaninov, A.A.; Reshetnyak, E.N.; Strel’nitskij, V.E. (Вопросы атомной науки и техники, 2014)
Comparative studies of the structure, mechanical and tribological properties of DLC coatings deposited in DC and DC with superimposed high current pulse modes of operation vacuum-arc plasma source with the graphite cathode are presented. Imposition the pulses of high current on DC vacuum-arc discharge allows both increase the deposition rate of DLC coating and reduce the residual compressive stress in the coatings what promotes substantial improvement the adhesion to the substrate. Effect of vacuum arc plasma filtration with Venetian blind filter on the deposition rate and tribological characteristics of the coatings analyzed.